Slurry composition for chemical mechanical polishing and method for manufacturing semiconductor device
By increasing the Ce3+ ratio of ceria particles and adjusting their Zeta potential, the problem that existing ceria slurry is difficult to reduce scratches and improve the removal speed of oxide film during grinding, and efficient oxide film removal and low defect grinding are achieved.
Patent Information
- Application Number
- CN202380076138.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-28
- Filing Date
- 2023-10-30
- Publication Date
- 2025-06-13
AI Technical Summary
It is difficult for the existing ceria slurry to reduce the grinding scratches while maintaining the grinding speed during grinding, and the ratio of Ce3+ to Ce4+ of ceria particles has not been optimized, which affects the removal speed of the oxide film.
By increasing the Ce3+ ratio of cerium oxide particles, although the particle size is small, the removal speed of the oxide film can be increased, and the Zeta potential of the cerium oxide particles can be converted to negative values by adding a surface treatment agent to adapt to different grinding processes.
It realizes efficient removal of oxide film at low content, and broadens the application range of nitride film grinding, reduces the occurrence of surface defects, and improves grinding efficiency.
Smart Images

Figure CN120153039A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a slurry composition for chemical mechanical polishing containing cerium oxide particles and a method for manufacturing a semiconductor device, and more particularly, to increasing the proportion of Ce on the surface of cerium oxide obtained by a synthesis method different from that of existing cerium oxide particles, so that although the particle size is small, a high oxide film removal rate can be achieved at a low content, and in combination with this, the Zeta potential on the surface of the cerium oxide particles can be converted by appropriate additives, so that a slurry composition for chemical mechanical polishing applicable to various polishing processes and a method for manufacturing a semiconductor device using the same can be obtained. 3+ Background Art
[0002] As semiconductor devices become diverse and highly integrated, more sophisticated patterning techniques are being used. Therefore, the surface structure of semiconductor devices is becoming more complex, and in order to improve the accuracy of photolithography, interlayer flatness is playing a very important role in each process. In the manufacture of semiconductor devices, a chemical mechanical polishing (CMP) process is used as such a planarization technique. For example, it is also widely used in the following processes: a process of removing an insulating film that is excessively formed for interlayer insulation; a planarization process of an insulating film for shallow trench isolation (STI) that insulates an interlayer dielectric (ILD) from a chip; and a process for forming a metal conductive film such as wiring, a contact slot, and a via contact.
[0003] For the CMP process, the polishing rate, the flatness of the polished surface, and the degree of scratch generation are important and are determined by CMP process conditions, the type of slurry, the type of polishing pad, and the like. High-purity cerium oxide particles are used in the cerium oxide slurry. In recent years, in the manufacturing process of semiconductor devices, further refined wiring has been required, but the generation of polishing scratches during polishing is a problem that needs to be overcome.
[0004] Existing cerium oxide slurries use particles with a particle size of 30 nm to 200 nm. Even if minute polishing scratches are generated during polishing, as long as they are smaller than the existing wiring width, it does not pose a problem. However, nowadays, continuous highly refined wiring needs to be achieved, so it has become a problem. In response to this, attempts are being made to reduce the average particle size of cerium oxide particles. However, when the average particle size of existing particles is reduced, the mechanical action decreases, and therefore, a problem of reduced polishing rate occurs.
[0005] Even if it is intended to control the polishing rate and polishing scratches by controlling the average particle size of cerium oxide particles, it is difficult to achieve the target level of polishing scratches while maintaining the polishing rate.
[0006] In addition, in the existing slurry compositions for chemical mechanical polishing, the cerium oxide particles do not optimize the ratio of Ce 3+ to Ce 4+ , and at the same time, the average particle size of the optimal level is not disclosed. Therefore, it is necessary to study the polishing slurry containing cerium oxide particles, and the cerium oxide particles can exhibit a high oxide film removal rate although the particle size is small by increasing the ratio of Ce 3+ on the surface of cerium oxide.
[0007] In addition, in the CMP process using a CMP slurry composition, by adjusting the Zeta potential to polish dissimilar films, or while increasing the polishing rate of the nitride film, a polishing stop function is achieved on the oxide film, etc. By adjusting the Zeta potential within the pH range, the utilization rate in the STI process can be broadened, so it is necessary to study the technology of adjusting the Zeta potential through additives.
[0008] As described above, the inventors of the present invention have developed cerium oxide particles with a size of 10 nm or less, the polishing rate of the oxide film obtained by precipitation in a solution being greatly improved, and by combining the cerium oxide particles having such optimized conditions with additives, a slurry composition capable of converting the Zeta potential into a negative value under weakly acidic conditions has been developed, thus completing the present invention. Summary of the Invention
[0009] Technical Problem
[0010] The present invention aims to solve the above problems, and an embodiment of the present invention provides a slurry composition for chemical mechanical polishing.
[0011] In addition, another embodiment of the present invention provides a method for manufacturing a semiconductor device.
[0012] The technical problems of the present invention are not limited to the above technical problems, and those skilled in the art can clearly understand many other technical problems not pointed out from the following description.
[0013] Technical Solution
[0014] As a technical solution for solving the above technical problems, an embodiment of the present invention provides a slurry composition for chemical mechanical polishing, which comprises: cerium oxide particles; a solvent; and a surface treatment agent, wherein the surface treatment agent converts the Zeta potential on the surface of the cerium oxide particles into a negative value (-), and in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0% by weight, the average light transmittance for light with a wavelength of 450 to 800 nm is 50% or more.
[0015] Before adding the surface treatment agent, the Zeta potential of the cerium oxide particles in the range of pH 2 to 8 may be 1 to 80 mV.
[0016] After adding the surface treatment agent, the Zeta potential of the cerium oxide particles in the range of pH 7 to 10 may be -80 to -1 mV.
[0017] Based on the total weight of the slurry composition for chemical mechanical polishing, the content of the surface treatment agent may be 0.001 to 1% by weight.
[0018] The surface treatment agent may be at least one selected from hydroxyethylidene diphosphonic acid (HEDP), aminotrimethylenephosphonic acid (ATMP), 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTC), ethylenediaminetetramethylenephosphonic acid (EDTMP), EDTA, nitrilotriacetic acid, diethylenetriaminepentaacetic acid (DTPA), N-hydroxyethyl ethylenediamine-N,N′,N′-triacetic acid (HEDTA), triethylenetetraminehexaacetic acid, 1,2-diaminopropanetetraacetic acid, 1,3-diamino-2-hydroxypropane-N,N,N′,N′-tetraacetic acid, N-hydroxyethyliminodiacetic acid, dihydroxyethylglycine (DHEG), ethylene glycol ether diamine tetraacetic acid, 1,2-diaminopropane-N,N,N′,N′-tetraacetic acid (PDTA), ethylenediaminetetraacetic acid (EDTA), and salts thereof.
[0019] The surface treatment agent may be hydroxyethylidene diphosphonic acid (HEDP) or ethylenediaminetetraacetic acid (EDTA).
[0020] Based on the total weight of the slurry composition for chemical mechanical polishing, the content of the cerium oxide particles may be 0.001 to 5% by weight.
[0021] The slurry composition for chemical mechanical polishing may further comprise a pH regulator, which may be an inorganic acid, an organic acid, an amino acid, imidazole, alkylamines, alkanolamines, quaternary ammonium bases, ammonia, or a combination thereof. Among them, the inorganic acid is one or more selected from sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid; the organic acid is one or more selected from acetic acid, citric acid, glutaric acid, glycolic acid, formic acid, lactic acid, malic acid, fumaric acid, maleic acid, oxalic acid, phthalic acid, succinic acid, and tartaric acid; the amino acid is one or more selected from lysine, glycine, alanine, arginine, valine, leucine, isoleucine, methionine, cysteine, proline, histidine, phenylalanine, serine, tris(hydroxymethyl)methylglycine, tyrosine, aspartic acid, tryptophan, and aminobutyric acid.
[0022] The pH value of the slurry composition for chemical mechanical polishing may be 2 to 10.
[0023] The slurry composition for chemical mechanical polishing may have a silicon oxide film polishing rate.
[0024] The secondary particle size of the cerium oxide particles measured by a dynamic light scattering particle size analyzer (DLS) may be 1 to 20 nm.
[0025] The primary particle size of the cerium oxide particles measured by a transmission electron microscope (TEM) may be 0.5 to 10 nm.
[0026] According to X-ray photoelectron spectroscopy (XPS) analysis, based on the total XPS peak area representing the Ce-O binding energy on the surface of the cerium oxide particles being 100%, the sum of the XPS peak areas representing the Ce 3+ -O binding energy may be 30% or more.
[0027] The cerium oxide particles may be prepared by a step of obtaining a dispersion of particles by precipitation in a solution containing a raw material precursor and at an acidic pH.
[0028] In addition, another embodiment of the present invention provides a method for manufacturing a semiconductor device, which includes a step of polishing using the slurry composition for chemical mechanical polishing.
[0029] Beneficial effects
[0030] According to the embodiments of the present invention, the manufactured cerium oxide particles increase the Ce on the surface of cerium oxide 3+The ratio, despite the small particle size, can have a high oxide film removal rate when included in a chemical mechanical polishing slurry at a low content. At the same time, when combined with the surface treatment agent disclosed in the present invention, it converts the surface Zeta potential of the cerium oxide particles into a negative value, thereby widely expanding applications such as nitride film polishing and obtaining more improved effects compared to when no additive is added.
[0031] In addition, according to an embodiment of the present invention, a cerium oxide particle for chemical mechanical polishing and a chemical mechanical polishing slurry composition containing the same can be provided, which can minimize the surface defects of a wafer and, different from the correlation between surface defects and oxide film removal rate that is considered a trade-off relationship in the prior art, can minimize surface defects while maximizing the oxide film removal rate.
[0032] The effects of the present invention are not limited to the above effects and should be understood to include all effects that can be inferred from the features of the invention described in the specification or claims of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a diagram showing the oxide film removal mechanism of an embodiment of the present invention.
[0034] Figures 2a to 2e is a cross-sectional view showing a method of manufacturing a semiconductor device according to an implementation example of the present invention, Figure 2f and Figure 2g respectively show the step process of chemical mechanical polishing and the structure of a chemical mechanical polishing (CMP) apparatus according to another implementation example of the present invention.
[0035] Figure 3 is an image obtained by visually observing a dispersion liquid in which existing cerium oxide particles are dispersed and a dispersion liquid in which cerium oxide particles according to an embodiment of the present invention are dispersed.
[0036] Figure 4 is a transmission electron microscope (TEM) image of cerium oxide particles according to an embodiment of the present invention.
[0037] Figure 5 shows scanning electron microscope (SEM) and transmission electron microscope (TEM) images of existing cerium oxide particles of a comparative example.
[0038] Figure 6 shows a TEM image of existing cerium oxide particles of a comparative example.
[0039] Figure 7These are the results of measuring cerium oxide particles of an embodiment of the present invention using a dynamic light scattering particle size analyzer (DLS). The analysis is the result of measurement using a Zetasizer Ultra from Malvern Corporation.
[0040] Figure 8 These are the X-ray diffraction (XRD) analysis results of cerium oxide particles of an embodiment of the present invention.
[0041] Figure 9 These are the XPS analysis results of cerium oxide particles of an embodiment of the present invention and existing cerium oxide particles of the 60 nm level.
[0042] Figure 10 These are the FT-IR spectroscopic analysis results of a powder composed of cerium oxide particles made according to an embodiment of the present invention and a powder composed of conventional cerium hydroxide particles.
[0043] Figure 11 These are the FT-IR spectroscopic analysis results of a powder composed of cerium oxide particles manufactured according to an embodiment of the present invention and a powder composed of particles formed under other conditions.
[0044] Figure 12 These are the results of the light transmittance measured by ultraviolet-visible (UV-Vis) spectrophotometry for a slurry containing cerium oxide particles of an embodiment of the present invention and slurries of Comparative Examples 1 to 4 containing existing cerium oxide particles. Detailed Description
[0045] Hereinafter, the present invention will be described in more detail. The present invention can be implemented in various different forms, and the present invention is not limited to the embodiments described herein. The present invention is defined by the appended claims.
[0046] In addition, the terms used in the present invention are only for describing specific embodiments and are not intended to limit the present invention. Unless clearly stated otherwise, a singular expression includes a plural expression. Unless there is a clearly contrary statement, "including" a certain component throughout the specification of the present invention does not mean excluding other components, but means that other components can be further included.
[0047] The "monodisperse" used in the present invention means that when cerium oxide particles are dispersed in a slurry, aggregation into secondary particles is suppressed, and thus the particle diameter of the primary particles is relatively maintained. This means that the secondary particle diameter (D50) measured by the dynamic light scattering (DLS) method is 3.0 times or less, 2.8 times or less, 2.5 times or less, 2.2 times or less, 2.0 times or less, or preferably 1.9 times or less of the primary particle diameter measured by TEM. In addition, when studying the particle size distribution, etc., it does not exclude the inclusion of inevitable impurities, etc. with relatively large sizes.
[0048] The term "transparent" used in the present invention means that when cerium oxide particles are dispersed in a slurry, the slurry composition is visually observed to be transparent. More specifically, the average light transmittance for light in the visible light region is 50% or more, preferably 70% or more, and more preferably 80% or more. This further indicates that the cerium oxide particles of the present invention are inhibited from aggregating into secondary particles, thereby relatively maintaining the particle size of the primary particles.
[0049] A polishing composition can be described by its polishing rate (i.e., removal rate) and its planarization efficiency. The polishing rate refers to the rate at which material is removed from the surface of a substrate, and is usually expressed in units of length (thickness) per unit time (e.g., ). Specifically, for example, the polishing pad first contacts the "high points" of the polishing surface and removes material to form a flat surface. A process that achieves a flat surface by removing less material is more efficient compared to a process that requires removing more material to achieve flatness.
[0050] The removal rate of the silicon oxide pattern tends to limit the rate of the dielectric polishing step in the STI process. Therefore, a higher removal rate of the silicon oxide pattern is beneficial for increasing the throughput of the equipment. However, when the removal rate of the capping layer is too fast, the trenches will be corroded due to excessive polishing of the oxide at the exposed trenches, and device defects will increase.
[0051] Hereinafter, the present invention will be described in detail.
[0052] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily implement them. However, the present invention can be implemented in various different forms and is not limited to the embodiments described herein.
[0053] Production Example 1. Production of Cerium Oxide Particles
[0054] The cerium oxide particles of an embodiment of the present invention can be chemically synthesized in a bottom-up manner. In an embodiment of the present invention, cerium oxide particles are manufactured by any one of the following cerium oxide particle manufacturing methods.
[0055] According to the manufacturing method of an embodiment of the present invention, first, about 2 to 4 kg of cerium nitrate is added to a sufficient amount of deionized water and stirred. Nitric acid is added to the precursor solution to adjust the pH value to below 1.0. Ammonia water is added to the prepared mixture and stirred until a precipitate is generated. It was confirmed that the pH of the stirred mixture was strongly acidic (below 2), and if left standing after stirring was completed, the product would precipitate rapidly. After removing the supernatant other than the precipitate, a specified amount of deionized water was added to generate a pale yellow cerium oxide particle dispersion. The prepared dispersion was circulated and filtered through a membrane filter to obtain a transparent yellow cerium oxide dispersion.
[0056] According to the manufacturing method of another embodiment of the present invention, first, 150 g of cerium oxide or cerium hydroxide is dispersed in 3 kg of deionized water and stirred sufficiently to prevent particle precipitation. Nitric acid is added to the mixture until the pH value reaches below 1.0. The mixture is added to a pulverizer filled with 0.05 mm zirconia beads and circulated and pulverized at 4,000 rpm. As the pulverization progresses, it is observed that the white opaque cerium oxide dispersion gradually turns into a yellow transparent cerium oxide dispersion. After the pulverization is completed, after allowing the prepared yellow transparent cerium oxide dispersion to precipitate, it is circulated and filtered through a membrane filter to obtain a pure yellow transparent cerium oxide dispersion.
[0057] According to the manufacturing method of another embodiment of the present invention, first, about 2 to 4 kg of ammonium cerium nitrate is added to a sufficient amount of ethanol and stirred. A basic imidazole solution is added to the precursor solution and stirred until a precipitate is generated. It was confirmed that the pH of the stirred mixture was strongly acidic (below 2), and if left standing after stirring was completed, the product would precipitate rapidly. After removing the supernatant other than the precipitate, a specified amount of deionized water was added to generate a cerium oxide particle dispersion. The prepared dispersion was circulated and filtered through a membrane filter to obtain a transparent cerium oxide dispersion.
[0058] According to the manufacturing method of another embodiment of the present invention, first, 1.1 kg of cerium nitrate and 10 kg of deionized water are mixed in a reaction vessel to prepare a strongly acidic solution. The stirring speed of the reaction vessel is maintained at 200 rpm, and room temperature is maintained. A 1:1 mixture of 25% ammonia solution and deionized water is prepared and added to the reaction vessel until the pH value reaches 7.0. After stirring for one hour, a 1:1 mixture of 70% nitric acid and deionized water is added until the pH value reaches 1.0. After raising the temperature of the reactor to 100 °C, a reaction is carried out for four hours. During the progress of the reaction, the pale purple large particles dissociate and yellow transparent cerium oxide nanoparticles are generated. The obtained particles are circulated using a membrane filter to remove impurities, and a pure cerium oxide nanoparticle dispersion is obtained.
[0059] Production Example 2. Production of CMP Slurry Containing Cerium Oxide Particles
[0060] The cerium oxide particles prepared in the above Manufacturing Example 1 were added to deionized water, and the abrasive concentration was adjusted to 0.05% by weight. Triethanolamine was added to adjust the pH value to 5.5, 8.0, 9.0, and 10.0, thereby preparing CMP slurries (2-1, 2-2, 2-3, 2-4).
[0061] According to Figure 3 , it can be observed with the naked eye that the turbidity of the slurry containing cerium oxide particles in the prior art is relatively high. On the contrary, it can be observed that the slurry containing the cerium oxide particles of the present invention is transparent. Therefore, it can be speculated that the cerium oxide particles have monodisperse characteristics.
[0062] Production Example 3. Production of CMP Slurry Containing a Surface Treatment Agent
[0063] The cerium oxide particles prepared in the above Manufacturing Example 1 were added to deionized water, and the abrasive concentration was adjusted to 0.05% by weight. 0.1% by weight of a surface treatment agent HEDP was added and stirred well. After stirring, triethanolamine was added to adjust the pH value to 5.5, 8.0, 9.0, and 10.0, respectively, thereby preparing CMP slurries (3-1, 3-2, 3-3, 3-4).
[0064] Experimental Example 1. SEM and TEM Analyses of Cerium Oxide Particles
[0065] The dispersion of Manufacturing Example 1 of an embodiment of the present invention was dried at about 80 to 90 °C to prepare cerium oxide particles (primary particles) in powder form (Sample A). On the other hand, cerium oxide particles used when preparing the dispersions of Comparative Examples 1 to 4 were prepared (Samples B1, B2, B3, and B4, respectively). Images of the above-prepared samples were taken using a TEM measuring instrument.
[0066] Figure 4 is a TEM image of the cerium oxide particles of an embodiment of the present invention.
[0067] Referring to Figure 4 , the TEM measurement results of the cerium oxide particles prepared according to an embodiment of the present invention show that the average particle size is about 4 nm or less (3.9 nm, 3.4 nm, and 2.9 nm, respectively, in repeated measurements). It can be seen that the average primary particle size of the cerium oxide particles of an embodiment of the present invention is 4 nm or less. In addition, it can be confirmed that the cerium oxide particles generally have the shape of spherical particles. Spherical cerium oxide particles with a small particle size and a relatively uniform size distribution can have a large specific surface area, and excellent dispersion stability and storage stability.
[0068] Figure 5SEM and TEM images of the existing cerium oxide particles of the comparative example are shown.
[0069] Refer to Figure 5 , the commercially available cerium oxide particles in the prior art have particle diameters corresponding to each size class, and all the particles separately prepared by the calcination method have a primary particle diameter of more than 10 nm on average. It can be confirmed that compared with the average particle diameter measured by TEM of the cerium oxide particles of an embodiment of the present invention shown in Figure 4 which is 4 nm or less, the cerium oxide particles in the prior art and the cerium oxide particles prepared by the conventional calcination method have significantly coarser particle diameters. On the contrary, it has been confirmed that the particle diameter (primary particle) of the cerium oxide particles of the present invention is formed small, and it can be predicted that the smaller the cerium oxide particle diameter, the more defects such as scratches generated on the surface of the film to be polished can be reduced.
[0070] In addition, Figure 6 TEM images of the existing cerium oxide particles of the comparative example are shown. Refer to Figure 6 , it can be confirmed that the cerium oxide particles in the prior art with a particle diameter of 10 nm or less include particles with edges and spherical particles, and the cerium oxide particles in the prior art with a particle diameter of 30 nm or more are angular particles with edges. On the contrary, as described above, the cerium oxide particles of the embodiment of the present invention are generally spherical. Since the cerium oxide particles of the present invention have a spherical particle shape and a small particle diameter, a large number of particles can be included. Therefore, the probability of surface defects generated during polishing of the silicon oxide film can be reduced, and the global flatness can be improved.
[0071] Experimental Example 2. Dynamic Light Scattering (DLS) Particle Size Analyzer Analysis of Cerium Oxide Particles
[0072] Particle Size Analyzer Analysis
[0073] The slurry composition of Production Example 2 of an embodiment of the present invention, the slurry compositions of Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 are prepared as samples. The prepared samples are respectively analyzed using a DLS device.
[0074] Figure 7 is the result of dynamic light scattering (DLS) analysis (Malvern, Zetasizer Ultra) of the cerium oxide particles of an embodiment of the present invention. In addition, Table 1 shows the D50 values obtained by dynamic light scattering (DLS) analysis of the cerium oxide particles of an embodiment of the present invention and the cerium oxide particles of multiple comparative examples.
[0075] Table 1:
[0076] Specimen D50 Value (nm) Example 1 of the Present Invention 5.78 Example 2 of the Present Invention: When an Additive is Added 6.88 Comparative Example 1 - Cerium Oxide Particles of Less than 10 nm in the Prior Art 33.6 Comparative Example 2 - Cerium Oxide Particles of 30 nm in the Prior Art 93.9 Comparative Example 3 - Cerium Oxide Particles of 60 nm in the Prior Art 138.7 Comparative Example 4 - Cerium Oxide Particles Produced by the Calcination Method 139.1
[0077] Refer toFigure 7 As shown in Table 1, upon measurement, the cerium oxide particles of the embodiments of the present invention have a secondary particle size D50 value of about 5.78 nm, which is 10 nm or less. Relative to the particle size of the primary particles measured by TEM in Experimental Example 1 (refer to Figure 4 ), it is about 148% - 199%, and it can be confirmed that almost no aggregation occurs in the slurry and the particles are monodispersed, and the particle size hardly changes.
[0078] On the contrary, the D50 particle size of the cerium oxide particles in the prior art measured by dynamic light scattering (DLS) is greater than 30 nm, and relative to the particle size of the primary particles measured by TEM, the D50 value of the secondary particle size of the 10 nm-class cerium oxide particles measured by dynamic light scattering (DLS) is about 336%. The cerium oxide particles in the prior art have a significantly larger secondary particle size, and thus it can be confirmed that a large amount of aggregation has occurred.
[0079] In particular, it can be confirmed that, as predicted by the inventors of the present invention, the secondary particle size of the cerium oxide particles of 10 nm or less prepared by the supercritical hydrothermal synthesis method or the wet method under alkaline conditions is significantly larger than the primary particle size.
[0080] In addition, it was confirmed that even when a surface treatment agent (Example 2) was contained as an additive, the monodispersity of the cerium oxide particles in the slurry could be maintained. Therefore, it was confirmed that the surface treatment agent in the present invention is suitable for use in combination with the cerium oxide particles of one embodiment of the present invention.
[0081] Therefore, compared with the cerium oxide particles in the prior art of a comparative example, the cerium oxide particles of one embodiment of the present invention have lower aggregability in the slurry and can be dispersed in the slurry in a more monodispersed form.
[0082] Experimental Example 3. X-ray Diffraction (XRD) Analysis of Cerium Oxide Particles
[0083] The dispersion liquid of Preparation Example 1 of one embodiment of the present invention was dried at about 80 - 90 °C to prepare cerium oxide particles (primary particles) in powder form (Sample A). The Sample A was analyzed using an XRD device (Rigaku, Ultima IV). At this time, the XRD was set to Cu Kα under the conditions of 40 kV and 40 mA.
[0084] Figure 8 is the X-ray diffraction (XRD) analysis result of the cerium oxide particles of one embodiment of the present invention.
[0085] The Sample A was subjected to XRD analysis, and as a result, Figure 8XRD spectrum of the form shown (X-axis: 2-theta (degree), Y-axis: intensity). The crystallite size calculated based on the spectrum is 3.25 nm. This is similar to the TEM analysis result of Experimental Example 1, and thus it can be confirmed that the particles of the present invention are single crystals.
[0086] Experimental Example 4. XPS Analysis of Cerium Oxide Particles
[0087] Figure 9 is the XPS analysis result of cerium oxide particles of an embodiment of the present invention and existing cerium oxide particles of 60 nm level. X-ray photoelectron spectroscopy (XPS) can measure the peaks of Ce-O binding energy of Ce appearing at 900.2 - 902.2 eV, 896.4 - 898.4 eV, 885.3 - 887.3 eV, and 880.1 - 882.1 eV when irradiated with soft X-ray, and analyze the atomic percentage (atomic%) through XPS fitting, thereby measuring the content of Ce 3+ and Ge 3+ in the cerium oxide particles. Table 2 is the XPS result data of the cerium oxide particles of the embodiment of the present invention. 4+
[0088] Table 2:
[0089]
[0090] Based on the above XPS analysis results, it can be known that according to the result of calculating the Ce 3+ content according to the above chemical formula, the Ce 3+ content is 30% or more. It can be seen that in the cerium oxide particles, Ce 3+ is the reactive sites, so the grinding amount can be increased. In the above manner, the comparison data with the cerium oxide particles in the prior art are shown in Table 3 together.
[0091] Table 3:
[0092]
[0093] As shown in Table 3, the content of Ce 3+ of the cerium oxide particles of an embodiment of the present invention is about 36.9 atomic percentage (atomic%), and it can be known from Table 1 that compared with the Ce 3+ The content is less than 14 atomic percent (atomic %), and compared with about 16.8% of cerium oxide particles with a size of 10 nm level prepared by hydrothermal synthesis method under supercritical or subcritical conditions recorded in the existing literature, it has a higher Ce 3+ content. When having a high level of surface Ce 3+ content as in the embodiments of the present invention, the polishing rate for a silicon-containing substrate can be improved through the chemical polishing mechanism of forming Si-O-Ce between silica and cerium.
[0094] Experimental Example 5. Confirmation of the Formation of Cerium Oxide Particles by Fourier Transform Infrared (FT-IR) Spectral Analysis
[0095] Figure 10 are the FT-IR spectral analysis results of the powder composed of cerium oxide particles prepared according to an embodiment of the present invention and the powder composed of conventional cerium hydroxide particles. After drying the dispersion liquid of Manufacturing Example 1 of an embodiment of the present invention at about 80 - 90 °C to prepare cerium oxide particles (primary particles) in powder form, the spectrum was obtained using an FT-IR spectrometer. In the analysis range of 600 - 4100 cm -1 , it was scanned more than once to draw a curve graph (in the FT-IR spectrum, the wave number (cm -1 ) can have an error range of ±10 cm -1 ).
[0096] According to Figure 10 the analysis results of the FT-IR spectrum, the powder composed of cerium oxide particles of an embodiment of the present invention has an infrared transmittance of about 92 - 93% in the range of 3000 cm -1 - 3600 cm -1 , and an infrared transmittance of about 93 - 95% in the range of 720 cm -1 - 770 cm -1 . In the FT-IR spectrum of the powder composed of conventional cerium hydroxide particles, the infrared transmittance in the range of 3000 cm -1 - 3600 cm -1 is 75 - 90%, and the infrared transmittance in the range of 720 cm -1 - 770 cm -1 is 97 - 99%. Comparing the two, it can be confirmed that the cerium oxide particles prepared according to an embodiment of the present invention show a weaker hydroxyl (O-H group) band of cerium hydroxide particles in the range of 3000 cm -1 - 3600 cm -1 than conventional cerium hydroxide particles, and in the range of 720 cm -1 - 770 cm -1A peak based on Ce-O stretching is formed within the range. Therefore, this result can indicate that the cerium compound prepared according to an embodiment of the present invention is cerium oxide.
[0097] As a comparative example, in cerium oxide particles synthesized by a wet method similarly to an implementation example of the present invention, when synthesized under alkaline conditions, as described above, cerium hydroxide is first formed and then converted into cerium oxide through a post-process. According to the Figure 11 results of this experiment shown as follows, when the particles synthesized under alkaline pH conditions are measured by FT-IR immediately after synthesis, peaks in the range of 3000 cm -1 to 3600 cm -1 and in the range of 720 cm -1 to 770 cm -1 indicating cerium hydroxide still appear, and multiple main peaks of cerium hydroxide in the above Figure 10 thus making it difficult to be regarded as containing only cerium oxide.
[0098] Experimental Example 6. Measurement of the Transmittance of the Slurry Containing Cerium Oxide Particles
[0099] A slurry composition (Sample A) was prepared in the same manner as in Production Example 2, except that the weight ratio of cerium oxide particles in the CMP slurry was 1% by weight. On the other hand, slurry compositions (Sample B1, B2, B3, and B4 in sequence) were prepared in the same manner as in Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4, respectively, except that the weight ratio of cerium oxide particles in the CMP slurry was 1% by weight. Using a UV-Vis spectrophotometer (JASCO), the transmittance of each sample for light in the range of 200 to 1100 nm was measured.
[0100] Figure 11 are the results of the transmittance measured by ultraviolet-visible (UV-Vis) spectrophotometry for slurries containing cerium oxide particles of an embodiment of the present invention and existing cerium oxide particles of Comparative Examples 1 to 4.
[0101] Cerium oxide particles of an embodiment of the present invention and multiple comparative examples were added to deionized water, and the abrasive concentration was adjusted to 1.0% by weight to prepare a CMP slurry and analyze the transmittance. At this time, the spectrum in the range of 200 to 1,100 nm was measured using a UV-vis spectrophotometer (Jasco UV-vis spectrophotometer).
[0102] Through the above UV-Vis analysis spectra, the transmittance (%) of Sample A, A2, and Sample B1 to B4 at wavelengths of 500 nm, 600 nm, and 700 nm was sorted out and shown in Table 4.
[0103] Table 4:
[0104]
[0105] Based on Figure 11 and Table 2, it can be confirmed that the average light transmittance of the slurry containing the cerium oxide particles of the present invention for light with a wavelength of 450 to 800 nm is 50% or more. In addition, it can be confirmed that the light transmittance for light with a wavelength of about 500 nm is 90% or more, and the light transmittance for light with wavelengths of about 600 nm and 700 nm is 95% or more.
[0106] Conversely, the light transmittance of the slurries containing cerium oxide particles in the prior art of Comparative Examples 1 to 4 (cerium oxide particles in the prior art at the 10 nm level, 30 nm level, and 60 nm level, and cerium oxide particles based on the calcination method) was measured. The light transmittance of Comparative Example 4 (calcined cerium oxide particles) was almost 0%, and the average light transmittance of the slurry of Comparative Example 1 containing commercially available cerium oxide particles in the prior art at the 10 nm level was less than 80%, and the light transmittance at a wavelength of 500 nm was less than 50%. The primary particle sizes of Comparative Examples 2 and 3 were 30 nm and 60 nm, respectively, which were relatively large, and the secondary particle sizes were also larger than those of the examples of the present invention (i.e., the cohesiveness in the slurry was strong). Therefore, the light transmittance in the visible light region was less than 20%.
[0107] Conversely, the light transmittance of the cerium oxide particles in one embodiment of the present invention in the visible light region is 90% or more, which means that the size of the primary particles of the cerium oxide particles of the present invention is small, and compared with the cerium oxide particles in the prior art, they are less aggregated into secondary particles. Generally, when the secondary particles are larger than 20 nm, the slurry composition can be observed to be opaque with the naked eye, and the light transmittance for wavelengths in the visible light region is less than 80%.
[0108] According to the slurry composition of the present invention, when the primary particle size of the cerium oxide particles is small and the cohesiveness to form secondary particles is weak, the dispersion stability is high. Therefore, the particles can be evenly distributed, and the number of particles in contact with the wafer increases. Therefore, the oxidation film polishing speed is excellent, and the particles themselves are small. Therefore, when using the slurry composition containing the particles to polish the film to be polished, it is possible to easily predict the probability of reducing defects such as scratches on the surface.
[0109] In addition, it can be confirmed that even when a surface treatment agent is contained as an additive, the light transmittance characteristics of the present invention remain at the same level. However, when the wrong additive is selected, the monodispersibility of the cerium oxide particles in one embodiment of the present invention in the slurry may be impaired. In view of this, the surface treatment agent selected in the present invention can meet the required characteristics without impairing the basic characteristics of the particles in the slurry.
[0110] Experimental Example 7. Comparison of the Oxide Film Polishing Rates of Cerium Oxide Particles
[0111] Prepare the slurry compositions of Preparation Examples 2-1 to 2-4 of an embodiment of the present invention as samples, respectively.
[0112] The polishing of the oxide film wafer using the above samples was carried out using a polishing machine ( LK CMP, Applied Materials). Specifically, a PE-TEOS silicon oxide film wafer (300 mm PE-TEOS Wafer) was mounted on a polishing pad (Platen), and the surface of the wafer was brought into contact with the polishing pad (IC1010, DOW) of the polishing machine. Next, the slurry composition as a sample was supplied at a rate of 200 mL / min, and the polishing pad (Platen) and the polishing pad of the polishing machine were rotated to perform a polishing process. At this time, the rotation speed of the polishing pad and the rotation speed of the head were 67 rpm / 65 rpm, the polishing pressure was 2 psi, and the polishing time was 60 seconds. On the other hand, the thickness of the silicon oxide film of the wafer was measured using ST5000 (Spectra Thick 5000ST, K-MAC). The results are shown in Table 5.
[0113] Table 5:
[0114]
[0115] As shown in Table 5, in the case of using the slurry composition of the embodiment, it was found that precipitation occurred in Preparation Example 2 without surface treatment when the pH value was 8.0 or higher. However, in Preparation Example 3 with surface treatment using a surface treatment agent, a relatively high oxide film removal rate could be achieved even at a high pH value.
[0116] Experimental Example 8. Defect Evaluation of Cerium Oxide Particles
[0117] Figure 12 and Figure 13 are images obtained by scanning the oxide wafer before and after CMP using a CMP slurry composition containing cerium oxide particles of an embodiment of the present invention and a CMP slurry composition containing cerium oxide particles with a size of 60 nm, respectively.
[0118] The surface analysis of the oxide wafer was carried out in a full wafer scan mode using an AIT-XP device.
[0119] Refer to Figure 12 and Figure 13, after performing CMP on the surface of an oxide wafer using a CMP slurry composition containing cerium oxide particles of an embodiment of the present invention, as a result of analyzing the surface of the oxide wafer before and after CMP, the number of defects before CMP was 6, and the number of defects after CMP was 1. Therefore, after performing CMP using an embodiment of the present invention, the defects on the surface of the oxide wafer were reduced. Additionally, in the CMP process, no scratches were generated on the surface of the wafer. Conversely, after performing CMP on the surface of an oxide wafer using a CMP slurry composition containing cerium oxide particles in the prior art, as a result of analyzing the surface of the oxide wafer before and after CMP, compared to the number of defects before CMP being 34, the number of defects after CMP increased to 64. From this, it can be seen that the cerium oxide particles in the prior art left scratches on the surface of the wafer. This indicates that since the particle size of the cerium oxide particles of an embodiment of the present invention is smaller than the particle size of the cerium oxide particles in the prior art, therefore, the probability of generating defects on the surface of the oxide wafer to be polished can be significantly reduced. Additionally, it can be fully speculated that the cerium oxide particles of an embodiment of the present invention are monodispersed in the slurry and are themselves minute particles. Therefore, even when additives are included, defects can be minimized.
[0120] Experimental Example 9. Analysis of the Change in Zeta Potential Depending on the Addition of the Surface Treatment Agent
[0121] Table 6:
[0122]
[0123] Referring to Table 6, it can be confirmed that when a surface treatment agent of an embodiment of the present invention is contained, the Zeta potential of the cerium oxide particles can be converted to a negative value. This is an effect obtained while not impairing the characteristics of the particles of an embodiment of the present invention in the slurry, and thus, it is worthy of attention.
[0124] Embodiment
[0125] The first embodiment of the present invention provides a slurry composition for chemical mechanical polishing, which comprises:
[0126] Cerium oxide particles; a solvent; and a surface treatment agent, which converts the Zeta potential on the surface of the cerium oxide particles to a negative value (-), and in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0% by weight, the average light transmittance for light with a wavelength of 450 to 800 nm is 50% or more.
[0127] Hereinafter, the slurry composition for chemical mechanical polishing of the first embodiment of the present invention will be described in detail.
[0128] Figure 1 is a diagram showing the oxide film removal mechanism of an embodiment of the present invention. AsFigure 1 As shown, only the Ce 3+ ions on the surface of cerium oxide particles can be activated to react smoothly with SiO 2
[0129] In one implementation example of the present invention, by including the surface treatment agent, a stable dispersion effect can be achieved for an alkaline pH. This is the main technical feature that differentiates the slurry composition for chemical mechanical polishing of the present invention from the prior art. Therefore, it will be described in detail below. In particular, this feature is combined with the unique cerium oxide particles of the present invention, thereby showing a unique effect. Therefore, it will be described in detail below.
[0130] In one implementation example of the present invention, the surface treatment agent can convert the surface Zeta potential of the cerium oxide particles from a positive value to a negative value while maintaining the unique properties of the cerium oxide particles in the slurry of one implementation example of the present invention.
[0131] As described below, the cerium oxide particles of one implementation example of the present invention are obtained by a wet method at an acidic pH and are obtained in the form of a dispersion. Even if a solvent is directly added thereto to prepare a slurry, ultrafine cerium oxide nanoparticles can have a monodispersed form without an additional redispersion process, and the Ce 3+ content also remains at a high level. They are particles with a high level of oxide film polishing speed when manufacturing a slurry composition for chemical mechanical polishing. As described above, the inventors of the present invention have confirmed through research that even if various additives used in the prior art are added to the cerium oxide particles of one implementation example of the present invention with inherent properties, it is difficult to exhibit the performance desired in the prior art. In addition, from the perspective of those skilled in the art using nanoparticles, a composition containing nanoparticles also needs to find and combine suitable various substances for specific nanoparticles to achieve the required characteristics or performance. The slurry composition of one implementation example of the present invention can provide a combination with an optimal additive, which can convert the Zeta potential of the particles to a negative (-) value while maintaining the excellent oxide film polishing speed performance of the cerium oxide particles to a certain extent.
[0132] In one embodiment of the present invention, based on the total weight of the slurry composition for chemical mechanical polishing, the content of the surface treatment agent may be 0.001% by weight or more, 0.002% by weight or more, 0.003% by weight or more, 0.004% by weight or more, or 0.005% by weight or more, and may be 1% by weight or less, 0.5% by weight or less, 0.1% by weight or less, 0.05% by weight or less, 0.03% by weight or less, 0.01% by weight or less. When the content of the surface treatment agent is less than 0.001% by weight based on the total weight of the slurry composition for chemical mechanical polishing, the content is too small to fully play the role of the surface treatment agent, so that the effect of improving the slurry stability cannot be affected. When it is greater than 1% by weight, the added surface treatment agent will hinder the polishing process of cerium oxide. Therefore, instead, it will reduce the polishing rate of the oxide film or become an impurity in the slurry composition.
[0133] In one embodiment of the present invention, the surface treatment agent may be at least one selected from hydroxyethylidene diphosphonic acid (HEDP), aminotrimethylenephosphonic acid (ATMP), 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTC), ethylenediaminetetramethylenephosphonic acid (EDTMP), EDTA, nitrilotriacetic acid, diethylenetriaminepentaacetic acid (DTPA), N-hydroxyethylenediamine-N,N',N'-triacetic acid (HEDTA), triethylenetetraminehexaacetic acid, 1,2-diaminopropanetetraacetic acid, 1,3-diamino-2-hydroxypropane-N,N,N′,N′-tetraacetic acid, N-hydroxyethyliminodiacetic acid, dihydroxyethylglycine (DHEG), ethylene glycol ether diamine tetraacetic acid, 1,2-diaminopropane-N,N,N′,N′-tetraacetic acid (PDTA), ethylenediaminetetraacetic acid (EDTA), and salts thereof. Preferably, the surface treatment agent may be hydroxyethylidene diphosphonic acid (HEDP) or ethylenediaminetetraacetic acid (EDTA).
[0134] Hereinafter, cerium oxide particles in one embodiment of the present invention will be described. In one embodiment of the present invention, the slurry composition for chemical mechanical polishing uses cerium oxide particles with excellent dispersion stability, especially excellent polishing rate for silicon oxide films.
[0135] In an implementation example of the present invention, the Zeta potential value of the cerium oxide particles contained in the slurry as abrasive particles may be positive before adding or introducing the surface treatment agent. Preferably, within the pH range of 2 to 8, the Zeta potential value may be 1 to 80 mV, 5 to 60 mV, or 10 to 50 mV. The Zeta potential value of the cerium oxide particles is positive, so that the polarity of the surface of the silicon oxide film is negative. Therefore, the polishing efficiency is slightly reduced due to the repulsive force between the cerium oxide particles and the surface of the silicon oxide film. After introducing the surface treatment agent, the Zeta potential of the cerium oxide particles within the pH range of 7 to 10 may be -80 to -1 mV, -60 to -5 mV, or -50 to -10 mV. By surface treatment, the Zeta potential value of the cerium oxide particles is made negative, thereby reducing the polishing efficiency of the nitride film.
[0136] In an implementation example of the present invention, the hardness of the cerium oxide particles is lower than that of silicon dioxide particles or alumina particles. However, based on the chemical polishing mechanism of forming Si-O-Ce bonds between silicon dioxide and cerium, the polishing speed for surfaces containing silicon such as glass or semiconductor substrates is very fast. Therefore, it is beneficial for polishing semiconductor substrates.
[0137] In an implementation example of the present invention, dynamic light scattering (DLS) analysis can be used to measure the particle size (secondary particles) of the cerium oxide particles in the slurry. The dynamic light scattering analysis can be measured by analysis equipment known to those skilled in the art. Preferably, it is measured using a particle size analyzer of Anton Parr company or ZetasizerUltra of Malvern company, but this is only an example and is not limited thereto. The above-mentioned secondary particles are formed by the aggregation of primary particles described later in the slurry. It can be seen that the larger the surface area of the particles, the larger the action range of the gravitational force, so they are prone to aggregation. In addition, when the pH range in the solution passes through the isoelectric point where the Zeta potential of the particles is 0, they will aggregate into secondary particles. As disclosed in many prior arts, the isoelectric point pH value of cerium oxide particles is about 7. When particles are synthesized under alkaline conditions in a wet process, it is necessary to adjust the pH and pass through the isoelectric point in order to manufacture the slurry, and it is difficult to have monodispersity in the slurry like the particles in an implementation example of the present invention.
[0138] In an implementation example of the present invention, the particle size of the cerium oxide particles measured by a dynamic light scattering particle size analyzer (DLS) may be 1 to 30 nm. In another implementation example of the present invention, it may be 29 nm or less, 27 nm or less, 25 nm or less, 23 nm or less, 22 nm or less, 20.8 nm or less, 20.5 nm or less, 20.2 nm or less, 20 nm or less, 19.8 nm or less, 19.5 nm or less, 19.2 nm or less, 18 nm or less, 17 nm or less, or 15 nm or less, and may be 1.2 nm or more, 1.4 nm or more, 1.5 nm or more, 1.8 nm or more, 2 nm or more, 3 nm or more, or 4 nm or more. When the secondary particle size is greater than the above range, it indicates that a large amount of primary particles agglomerate in the slurry composition, and at this time, it is difficult to regard it as a monodisperse slurry. When the secondary particle size is less than the above range, the grinding speed for the target film will be overly hindered, resulting in a reduction in grinding efficiency.
[0139] In an implementation example of the present invention, the particle size (primary particles) of the cerium oxide particles can be measured using a transmission electron microscope (TEM). In an implementation example of the present invention, the particle size of the cerium oxide particles measured by a transmission electron microscope (TEM) may be 11 nm or less. In another implementation example, it may be 10.8 nm or less, 10.5 nm or less, 10.2 nm or less, 10 nm or less, 9.5 nm or less, 9.0 nm or less, 8.5 nm or less, 8.0 nm or less, 7.5 nm or less, 7.0 nm or less, 6.5 nm or less, 6.0 nm or less, 5.5 nm or less, 5.0 nm or less, 4.5 nm or less, or 4.0 nm or less, and may be 0.3 nm or more, 0.5 nm or more, 0.7 nm or more, 1.0 nm or more, 1.1 nm or more, 1.2 nm or more, 1.3 nm or more, 1.4 nm or more, 1.5 nm or more, 1.6 nm or more, 1.7 nm or more, 1.8 nm or more, 1.9 nm or more, 2.0 nm or more, 2.1 nm or more, 2.2 nm or more, 2.3 nm or more, or 2.4 nm or more. When the particle size of the cerium oxide particles is less than 0.3 nm, the crystallinity decreases, and the grinding speed for the target film decreases excessively, resulting in a reduction in grinding efficiency. On the contrary, when it is greater than 11 nm, there is a risk of generating a large number of surface defects such as scratches. In addition, in an implementation example of the present invention, the average particle size of the cerium oxide particles measured by the transmission electron microscope (TEM) may be 0.5 to 10 nm, preferably 1 to 10 nm, and more preferably 2 to 9 nm.
[0140] To describe the cerium oxide particles of an embodiment of the present invention, when the particle size of the cerium oxide particles measured by a dynamic light scattering (DLS) particle size analyzer is set as a, and the particle size of the cerium oxide particles measured by a transmission electron microscope (TEM) is set as b, the cerium oxide particles can satisfy the following formula 1.
[0141] Formula 1:
[0142] a ≤ 2.2b
[0143] This characteristic can be used as an index indicating that the cerium oxide particles of the present invention have low cohesiveness when dispersed in a slurry. When the coefficient of b is greater than 2.2, it indicates that a large amount of aggregation has occurred in the slurry, which means that it is difficult to suppress wafer surface defects during grinding due to the coarsening of the particle size.
[0144] In an embodiment of the present invention, the particle size (primary particle) of the cerium oxide particles can be measured by X-ray diffraction (XRD) analysis. In an embodiment of the present invention, the particle size of the cerium oxide particles measured by X-ray diffraction (XRD) analysis can be 11 nm or less. In another embodiment, it can be 10.8 nm or less, 10.5 nm or less, 10.2 nm or less, 10 nm or less, 9.5 nm or less, 9.0 nm or less, 8.5 nm or less, 8.0 nm or less, 7.5 nm or less, 7.0 nm or less, 6.5 nm or less, 6.0 nm or less, 5.5 nm or less, 5.0 nm or less, 4.5 nm or less, or 4.0 nm or less, and can be 0.3 nm or more, 0.5 nm or more, 0.7 nm or more, 1.0 nm or more, 1.1 nm or more, 1.2 nm or more, 1.3 nm or more, 1.4 nm or more, 1.5 nm or more, 1.6 nm or more, 1.7 nm or more, 1.8 nm or more, 1.9 nm or more, 2.0 nm or more, 2.1 nm or more, 2.2 nm or more, 2.3 nm or more, or 2.4 nm or more. When the particle size of the cerium oxide particles is less than 0.3 nm, the crystallinity decreases, and the grinding rate for the target film decreases excessively, resulting in a decrease in grinding efficiency. On the contrary, when it is greater than 11 nm, there is a risk of generating a large number of surface defects such as scratches. In addition, in an embodiment of the present invention, the average particle size of the cerium oxide particles measured by the X-ray diffraction (XRD) analysis can be 0.5 - 10 nm, preferably 1 - 10 nm, and more preferably 2 - 9 nm.
[0145] In an embodiment of the present invention, XPS can be used to analyze Ce on the surface of the cerium oxide particles 3+Analyze the content. For example, the thetaprobe base system manufactured by Thermo Fisher Scientific Co can be used. The Ce on the surface of the cerium oxide abrasive particles can be calculated based on the following Chemical Formula 1 3+ content.
[0146] Chemical Formula 1:
[0147] Ce 3+ Content (%) = (Ce 3+ peak area) / [(Ce 3+ peak area)+(Ce 4+ peak area)]
[0148] In one implementation example, according to the X-ray photoelectron spectroscopy (XPS) analysis on the surface of the cerium oxide particles, the XPS peaks representing the Ce 3+ Ce-O binding energy appear at 900.2 - 902.2 eV, 896.4 - 898.4 eV, 885.3 - 887.3 eV, and 880.1 - 882.1 eV. Specifically, according to the X-ray photoelectron spectroscopy (XPS) analysis on the surface of the cerium oxide particles, the XPS peaks representing the Ce 3+ Ce-O binding energy include a first peak at 900.2 - 902.2 eV, a second peak at 896.4 - 898.4 eV, a third peak at 885.3 - 887.3 eV, and a fourth peak at 880.1 - 882.1 eV.
[0149] In one implementation example of the present invention, relative to the total area of the XPS peaks, the area of the first peak can be 3% or more or 4% or more, the areas of the second and fourth peaks can be 5% or more, 7% or more, or 10% or more respectively, and the area of the third peak can be 4% or more, 5% or more, or 6% or more.
[0150] In addition, in one implementation example of the present invention, according to the X-ray photoelectron spectroscopy (XPS) analysis, the ratio of the sum of the XPS peak areas representing the Ce 3+ Ce-O binding energy to the total sum of the XPS peak areas representing the Ce-O binding energy on the surface of the cerium oxide particles can be 0.29 - 0.70. In another implementation example of the present invention, representing Ce 3+The ratio of the sum of the XPS peak areas of the Ce-O binding energy to the total sum of the XPS peak areas representing the Ce-O binding energy on the surface of the cerium oxide particles may be 0.18 or more, 0.19 or more, 0.192 or more, 0.195 or more, 0.198 or more, 0.20 or more, 0.202 or more, 0.205 or more, 0.208 or more, 0.21 or more, 0.22 or more, 0.24 or more, 0.25 or more, 0.27 or more, 0.28 or more, 0.30 or more, 0.32 or more, or 0.35 or more, and may be 0.90 or less, 0.88 or less, 0.85 or less, 0.83 or less, 0.80 or less, 0.77 or less, 0.75 or less, 0.72 or less, 0.71 or less, 0.705 or less, 0.70 or less, 0.695 or less, 0.69 or less, 0.68 or less, 0.67 or less, 0.66 or less, 0.65 or less, 0.64 or less, 0.63 or less, 0.62 or less, 0.61 or less, or 0.60 or less. When it is less than the above range, sufficient Ce cannot exist on the surface of the cerium oxide particles. 3+ , therefore, it is difficult to expect a sufficient increase in the oxidation film polishing rate. When it is greater than the above range, considering the oxidation number, it is difficult to interpret that it exists in the form of cerium oxide particles.
[0151] That is, in one implementation example of the present invention, according to X-ray photoelectron spectroscopy (XPS) analysis, the Ce 3+ content on the surface of the cerium oxide particles for chemical mechanical polishing may be 18 atomic % or more, 19 atomic % or more, 20 atomic % or more, 22 atomic % or more, 24 atomic % or more, 25 atomic % or more, 27 atomic % or more, 28 atomic % or more, 30 atomic % or more, 32 atomic % or more, or 35 atomic % or more, and may be 90 atomic % or less, 88 atomic % or less, 85 atomic % or less, 83 atomic % or less, 80 atomic % or less, 77 atomic % or less, 75 atomic % or less, 72 atomic % or less, or 70 atomic % or less.
[0152] The cerium oxide particles of one implementation example of the present invention have the characteristic of a high Ce 3+ content on the particle surface. This is because in one implementation example of the present invention, the process of particle synthesis in the liquid phase by a wet process is carried out under acidic conditions. Generally, a cerium precursor substance containing trivalent cerium maintains the cerium trivalent state at an acidic pH. In the manufacturing method of one implementation example of the present invention, the overall process of particle synthesis does not include a conversion to a basic pH. Therefore, the content of cerium trivalent on the surface of the synthesized particles is high. This characteristic of the cerium trivalent content on the surface of such cerium oxide particles is related to whether surface defects are formed and maintained in the manufacturing process. Therefore, it is a characteristic independent of technical characteristics such as the above-mentioned primary particle or secondary particle size. As described above, the Ce 3+The content is high. When the Ce on the surface 3+ When the content is relatively high, it can improve the polishing rate of the oxide film.
[0153] In one implementation example of the present invention, when Fourier-transform infrared (FT-IR) spectroscopy is performed on the powder composed of the cerium oxide particles, in the spectrum specific to the FT-IR spectroscopy, in the range of 3000 cm-1 to 3600 cm-1, the infrared transmittance of the powder composed of the cerium oxide particles can be 90% or more, or 100% or less, 97% or less, or 95% or less. Additionally, in one implementation example of the present invention, in the range of 720 cm-1 to 770 cm-1, the infrared transmittance of the powder can be 96% or less, and can be 85% or more, 88% or more, more preferably 90% or more, and even more preferably 92% or more. In the range of 3000 cm-1 to 3600 cm-1 of the FT-IR spectrum, the infrared transmittance having a value within the above range indicates that the hydroxyl (O-H group) band is relatively weak, which is different from the FT-IR spectrum of the powder composed of cerium hydroxide particles. Additionally, in the range of 720 cm-1 to 770 cm-1 of the FT-IR spectrum of the powder composed of the cerium oxide particles of one embodiment of the present invention, there is a peak indicating the infrared transmittance within the above range, which can indicate the occurrence of Ce-O stretching within the above range, and this can indicate that the particles manufactured according to one embodiment of the present invention exhibit the characteristics of cerium oxide particles. In particular, in the wet method of the cerium oxide particle manufacturing method, when synthesized under alkaline conditions, additional heat treatment or long-term exposure to oxygen and other processes for conversion to cerium oxide are inevitably accompanied. Therefore, when measuring FT-IR immediately after the particle synthesis process and before this subsequent process, multiple peaks related to cerium hydroxide will be detected. However, the cerium oxide particles of one implementation example of the present invention do not adopt the process of first forming cerium hydroxide and then converting it to cerium oxide. Therefore, even when measuring immediately after synthesis, only multiple peaks related to cerium oxide will be detected.
[0154] In one implementation example of the present invention, the cerium oxide primary particles can be one or more selected from spherical, cubic shape, tetragonal shape, orthorhombic shape, rhombohedral shape, monoclinic shape, hexagonal shape, triclinic shape, and cuboctahedron shape, and spherical particles are preferred.
[0155] In one implementation example of the present invention, the cerium oxide particles can be made by a method of growing particles through chemical synthesis, preferably in a bottom-up manner. As the synthesis method of the cerium oxide particles, methods such as sol-gel method, supercritical reaction, hydrothermal reaction or coprecipitation method can be used, but are not limited thereto. The bottom-up method, as a kind of chemical synthesis that has attracted much attention in recent years, is a method of growing starting materials of atoms or molecules into nanoparticles through chemical reactions.
[0156] In one implementation example of the present invention, the polishing composition contains wet-process cerium oxide particles. The wet-process cerium oxide particles can be any suitable wet-process cerium oxide particles. For example, the wet-process cerium oxide particles can be precipitated cerium oxide particles or polycondensed cerium oxide particles including colloidal cerium oxide particles.
[0157] In one implementation example of the present invention, the wet-process cerium oxide particles preferably have defects on the surface of the particles. Although not intended to be combined with any specific theory, the crushing of cerium oxide particles will cause defects to appear on the surface of the cerium oxide particles, and such defects will affect the performance of the cerium oxide particles in the chemical mechanical polishing composition. In particular, the cerium oxide particles may break when crushed, thus exposing a relatively less favorable surface state. This process is relaxation, and atoms with limited reconstruction ability and limited recovery ability to a more favorable state around the surface of the cerium oxide particles will form defects on the particle surface.
[0158] In one implementation example of the present invention, when generating secondary particles of the polishing material, the solvents each have an inherent dielectric constant value, and in the nucleation and crystal growth during the synthesis of the powder, the dielectric constant of the solvent will change the surface energy or surface charge, etc., thus affecting the condensation and growth of the nuclei, and this will affect the size and shape of the powder, etc. The dielectric constant of the solvent is proportional to the surface potential (Zeta potential) of the particles dispersed in the solvent. When the Zeta potential is small, the surface repulsion between the fine particles or between the nuclei generated by the reaction is small. Therefore, it is in an unstable state, causing the fine particles or nuclei to condense rapidly. At this time, the magnitudes of the surface repulsions between the fine particles or nuclei are all similar, so they can condense with a uniform size. The secondary particles condensed in this way are formed by the primary fine particles or nuclei growing into larger-sized particles through particle coalescence processes such as stronger condensation or Ostwald ripening according to reaction conditions such as temperature and concentration.
[0159] When using the cerium oxide as a polishing material, due to the strong reactivity between cerium oxide and silicon oxide, Si-O-Ce chemical bonding occurs. Therefore, different from mechanical polishing that only removes the hydrated layer formed on the surface, cerium oxide removes silicon oxide blocks from the surface of the silicon oxide film in a peeling manner, thereby polishing the silicon oxide film. In addition, the cerium oxide powder in the embodiment of the present invention has a small particle size, so the strength is low, and the global flatness of polishing is excellent. At the same time, the problem of micro-scratches formed by large particles can also be solved.
[0160] Hereinafter, a slurry composition for chemical mechanical polishing containing the cerium oxide particles and a surface treatment agent according to an embodiment of the present invention will be described in detail.
[0161] In one embodiment of the present invention, in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0% by weight, the average light transmittance for light with a wavelength of 450 to 800 nm may be 50% or more, or 60% or more. The average light transmittance is preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more. In addition, in another embodiment of the present invention, the light transmittance for light with a wavelength of 500 nm may be 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, or 80% or more. In addition, the light transmittance for light with a wavelength of 600 nm may be 75% or more, 80% or more, 85% or more, or 90% or more. In addition, the light transmittance for light with a wavelength of 700 nm may be 87% or more, 90% or more, 93% or more, or 95% or more. The light transmittance value of the slurry composition satisfying the above range means that the primary particle size of the cerium oxide particles in one embodiment of the present invention is small per se, and compared with the cerium oxide particles in the prior art, they aggregate into secondary particles less. When the cohesiveness is low, the dispersion stability is high, so the particles can be evenly distributed, and the number of particles in contact with the wafer increases. Therefore, the oxidation film polishing speed is excellent, and the particles themselves are tiny. Therefore, when using the slurry composition containing the particles to polish the film to be polished, the probability of defects such as scratches on the surface can be reduced. That is, based on the primary particles, the cerium oxide particles of 10 nm or less in size have a higher light transmittance in the visible light region, and the silicon oxide film polishing speed is more excellent. In addition, even if the surface treatment agent is further included as an additive, this light transmittance characteristic can be maintained.
[0162] In one embodiment of the present invention, based on the total weight of the slurry composition for chemical mechanical polishing, the content of the cerium oxide particles may be 5 wt% or less. In another embodiment of the present invention, based on the total weight of the slurry composition for chemical mechanical polishing, the content of the cerium oxide particles may be 4 wt% or less, 3 wt% or less, 2 wt% or less, 1.5 wt% or less, 1 wt% or less, 0.8 wt% or less, 0.5 wt% or less, 0.4 wt% or less, 0.3 wt% or less, 0.2 wt% or less, less than 0.2 wt%, 0.19 wt% or less, 0.15 wt% or less, 0.12 wt% or less, 0.10 wt% or less, 0.09 wt% or less, or 0.07 wt% or less, and may be 0.0001 wt% or more or 0.001 wt% or more. Although the slurry composition for chemical mechanical polishing of the present invention uses a slurry with the same polishing rate, even if a lower content of the cerium oxide particles is added based on the total weight of the slurry composition for chemical mechanical polishing, higher polishing efficiency of the oxide film can be achieved.
[0163] In one embodiment of the present invention, the pH value of the composition may be 2 to 10. In one embodiment of the present invention, the slurry composition for chemical mechanical polishing may contain one or more acidic or basic pH regulators and buffers capable of adjusting the pH in consideration of the final pH of the composition, polishing rate, polishing selectivity ratio, etc. The above pH regulator for adjusting the pH may use a pH regulator capable of adjusting the pH without affecting the properties of the slurry composition for chemical mechanical polishing. In one embodiment of the present invention, the pH regulator may be an acidic pH regulator or a basic pH regulator to achieve an appropriate pH value.
[0164] In an implementation example of the present invention, for example, the pH regulator may be an inorganic acid, an organic acid, an amino acid, imidazole, an alkylamine, an alkanolamine, a quaternary ammonium base, ammonia, or a combination thereof, wherein the inorganic acid is one or more selected from sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid, the organic acid is one or more selected from acetic acid, citric acid, glutaric acid, glycolic acid, formic acid, lactic acid, malic acid, carotinic acid, maleic acid, oxalic acid, phthalic acid, succinic acid, and tartaric acid, and the amino acid is one or more selected from lysine, glycine, alanine, arginine, valine, leucine, isoleucine, methionine, cysteine, proline, histidine, phenylalanine, serine, tris(hydroxymethyl)methylglycine, tyrosine, aspartic acid, tryptophan, and aminobutyric acid. In particular, the pH regulator may be triethanolamine, tetramethylammonium hydroxide (TMAH or TMAOH), or tetraethylammonium hydroxide (TEAH or TEA-OH). Additionally, for example, the pH regulator may be one or more selected from ammoniummethyl propanol (AMP), tetra methyl ammonium hydroxide (TMAH), potassium hydroxide, sodium hydroxide, magnesium hydroxide, rubidium hydroxide, cesium hydroxide, sodium bicarbonate, sodium carbonate, triethanolamine, tromethamine, and nicotinamide. Preferably, the pH regulator may be triethanolamine or aminobutyric acid.
[0165] In an implementation example of the present invention, the solvent may be any solvent used in the slurry composition for chemical mechanical polishing. For example, deionized water may be used, but the present invention is not limited thereto. Additionally, ultrapure water is preferably used. The content of the solvent may be the remaining content obtained by subtracting the content of the cerium oxide particles and other additional additives from the total amount of the slurry composition for chemical mechanical polishing. In an implementation example of the present invention, the solvent includes water (e.g., deionized water) as an aqueous carrier and one or more water-miscible organic solvents. The organic solvents that can be used include: alcohols, such as allyl alcohol, isopropyl alcohol, ethanol, 1-propanol, methanol, 1-hexanol, etc.; aldehydes, such as acetaldehyde, etc.; ketones, such as acetone, diacetone alcohol, methyl ethyl ketone, etc.; esters, such as ethyl formate, propyl formate, ethyl acetate, methyl acetate, methyl lactate, butyl lactate, ethyl lactate, etc.; ethers including sulfoxides (e.g., dimethyl sulfoxide (DMSO)), tetrahydrofuran, dioxane, diethylene glycol dimethyl ether, etc.; amides, such as N,N-dimethylformamide, dimethylimidazolinone, N-methylpyrrolidone, etc.; polyols and their derivatives, such as ethylene glycol, glycerol, diethylene glycol, diethylene glycol monomethyl ether, etc.; and nitrogen-containing organic compounds, such as acetonitrile, pentylamine, isopropylamine, dimethylamine, etc.
[0166] In one embodiment of the present invention, the polishing composition further optionally contains one or more other additives. The polishing composition may include surfactants and / or rheology modifiers such as thickeners and setting agents (e.g., high molecular weight rheology modifiers such as polyurethanes), biocides (e.g., KATHON TM LX), etc. Suitable surfactants include, for example, cationic surfactants, anionic surfactants, anionic polyelectrolytes, nonionic surfactants, amphoteric surfactants, fluorosurfactants, and mixtures thereof.
[0167] In one embodiment of the present invention, the slurry composition for chemical mechanical polishing has excellent dispersion stability, especially a high polishing rate for silicon oxide films.
[0168] In one embodiment of the present invention, the polishing rate of the silicon oxide film of the slurry composition for chemical mechanical polishing can be or more, preferably or more, more preferably or more. In particular, in the slurry composition for chemical mechanical polishing using the cerium oxide particles of one embodiment of the present invention, even when the cerium oxide particles are in a low content range, due to their small particle size, the number of particles contained is more than that of the slurry composition containing conventional cerium oxide particles, and the Ce 3+ content on the surface is high, resulting in an increase in Si-O-Ce bonds. Therefore, the polishing rate of the silicon oxide film can be significantly improved.
[0169] In addition, the second embodiment of the present invention provides a method for manufacturing a semiconductor device, which includes a step of polishing using the slurry composition for chemical mechanical polishing.
[0170] The detailed description of the parts repeated with the first embodiment of the present invention is omitted, but the description content of the first embodiment of the present invention is equally applicable to the second embodiment.
[0171] Hereinafter, the method for manufacturing a semiconductor device according to the second embodiment of the present invention will be described in detail.
[0172] First, according to the shallow trench isolation (STI) Routine process, in the process for planarization of the insulating film, photolithography, etching, and cleaning (polishing) can be classified as general basic processes.
[0173] To separate the device, the lithography process can be started as the first step. The lithography process can be implemented on an auxiliary device called Track and an exposure machine that performs exposure to copy a circuit pattern (Mask) onto a wafer. First, a photosensitive agent (Photo Resistor) is applied. Since the viscosity of the photosensitive agent is high, it needs to be thinly coated on the insulating film while rotating the wafer. Only when the coated photosensitive agent is highly uniform will the photosensitive depth be appropriate. When exposure is performed, if the photosensitive depth is insufficient, photosensitive agent residues will be left during development, and in the subsequent etching process, the lower film (insulating layer) cannot be smoothly removed. After photosensitization, the wafer is transferred back to the Track device to perform the development process of removing the photosensitive part.
[0174] As the second step, the etching of STI is a process of removing the insulating layer (oxide layer + nitride layer) and a part of the substrate directly below the developed part (the part where the photosensitive film is removed). The etching process can use a dry or wet process. The dry etching method is usually a method of etching using a plasma state. Compared with the wet (liquid) method, the dry method does not etch the sidewalls (anisotropic etching), only etches the bottom, so it is beneficial for shaping the trench shape. At this time, over-etching may occur, so it is necessary to perform it after accurately calculating the etching end point. After etching, residues will be left, so it is necessary to process them.
[0175] After etching the trench shape, the photosensitive agent layer is no longer useful, so it can be removed by ashing. Preferably, the ashing process is performed using plasma, so that ashing can be performed more precisely. The shape of the semiconductor device after completing the ashing process is shown in Figure 2a in.
[0176] The manufacturing method of a semiconductor device according to an embodiment of the present invention may include: a step of simultaneously polishing a silicon oxide film, a silicon nitride film, and a polysilicon film using the slurry composition for chemical mechanical polishing.
[0177] Figures 2a to 2e is a cross-sectional view showing a manufacturing method of a semiconductor device according to an embodiment of the present invention.
[0178] Referring to Figure 2a , a trench 13 can be formed in the upper film 11 on the lower film 10. As an example, an upper film 11 can be formed on the lower film 10, and a nitride film (polishing stop film) 12 can be formed on the upper film 11. The lower film 10 can include any material film. For example, the lower film 10 can be an insulating film, a conductive film, a semiconductor film, or a semiconductor wafer (substrate). The upper film 11 can include an insulating film (oxide film), a conductive film, a semiconductor film, or a combination thereof.
[0179] When the upper film 11 includes a plurality of stacked insulating films, these insulating films can be of the same type or different types from each other. As an example, the upper film 11 may include a plurality of silicon oxide films and a plurality of silicon nitride films that are alternately and repeatedly stacked. The upper film 11 may further include a semiconductor film and a lower insulating film below the plurality of silicon oxide films and the plurality of silicon nitride films. For example, the lower insulating film may be disposed below the semiconductor film.
[0180] For example, silicon nitride (e.g., SiN), polysilicon, metal nitride (e.g., TiN), metal, etc. can be deposited so that the nitride film (etch stop film) 12 has a relatively large thickness (e.g., ). The trench 13 can be formed by an etching process or a drilling process. The trench 13 can have a depth that can penetrate the nitride film (etch stop film) 12 and the upper film 11 to reach the lower film 10. For example, the trench 13 can have a depth sufficient to expose the lower film 10.
[0181] Referring to Figure 2b , in STI, an oxide film can be formed in a double structure. First, before officially filling the trench 13 that ensures space with an insulating material, a linear (Liner) oxide film is thinly covered in a diffusion manner as the first insulating film 14. This is to smoothly form the second insulating film on the silicon substrate by CVD deposition in subsequent steps. According to another implementation example of the present invention, when filling the trench 13 by high-density plasma CVD (HDPCVD), it can also play a role in avoiding damage caused by high-energy plasma. According to an implementation example of the present invention, the first insulating film (linear oxide film) can be formed into a thin film such as a gate oxide film by introducing oxygen into a diffusion furnace (Furnace) and heating it at a high temperature. Additionally, according to another implementation example of the present invention, a nitride film can also be used instead of the oxide film.
[0182] Referring to Figure 2c , a plurality of insulators can be deposited to form the first insulating film 14 and the second insulating film 15 that fill the trench 13. The density and deposition rate of the first insulating film 14 and the second insulating film 15 can be different from each other. According to an embodiment of the present invention, the first insulating film 14 can be deposited and patterned from a high-density insulator. The second insulating film 15 can be deposited from a low-density insulator. As an example, the first insulating film 14 can be deposited and patterned from a high-density plasma (HDP) oxide. The first insulating film 14 can be formed in a shape that extends along the inner surface of the trench 13. For example, the first insulating film 14 can be in a U-shaped or tubular shape that opens upward.
[0183] Since the first insulating film 14 has a high density, it is difficult for voids to be generated in the first insulating film 14. Therefore, during subsequent heat treatment processes, cracks caused by voids can be prevented or significantly reduced. For example, the second insulating film 15 can be formed by filling the trench 13 in which the first insulating film 14 is formed with tetraethyl orthosilicate (TEOS) oxide and depositing it to a thickness sufficient to cover the polishing stop film 12. The second insulating film 15 can be formed at a deposition rate faster than that of the first insulating film 14. Due to the fast deposition rate of the second insulating film 15, the trench 13 can be filled with the second insulating film 15 relatively quickly.
[0184] According to another implementation example of the present invention, although not shown, a part of the second insulating film 15 can be removed so that the second insulating film 15 remains on the trench 13. For example, the second insulating film 15 can be selectively removed using a photolithography process and an etching process to define or open a specific area such as a cell storage area of a semiconductor device. Therefore, a part or all of the second insulating film 15 on the polishing stop film 12 can be removed, and the second insulating film 15 can remain on the trench 13. The opening process of the specific area can be selectively performed and is not necessary.
[0185] Refer to Figure 2d , a planarization process can be performed on the second insulating film 15. For example, the second insulating film 15 can be planarized by a chemical mechanical polishing (CMP) process. The chemical mechanical polishing process can be continued until the nitride film (polishing stop film) 12 is exposed. The chemical mechanical polishing process can be performed after the formation of the second insulating film 15 in Figure 2b . At this time, the surface on the nitride film (polishing stop film) 12 is relatively flat, or even if it is not flat, its non-flatness is not serious. Therefore, the chemical mechanical polishing process can be easily performed.
[0186] Next, refer to Figure 2e , the nitride film can be removed to form STI. The purpose of the nitride film is to protect the upper film 11 from being affected by the first insulating film 14. The upper film 11 can be a gate oxide film that requires thinness and high reliability, so careful operation is required. When the nitride film is removed by etching (wet method), the wafer can be immersed in a chemical solution so that only the nitride film is etched and the oxide film is not etched. For this purpose, a solution with a high selectivity ratio (etching ratio) for the nitride film can be used. In another implementation example of the present invention, the nitride film can be removed by CMP. At this time, it is not necessary to etch the nitride film, but physical damage may be caused to the oxide film. Therefore, it is preferably to chemically treat the nitride film by etching to protect the oxide film.
[0187] According to another implementation example of the present invention, after the gap filling, the first insulating film 14 and the second insulating film 15 on the upper part of the nitride film (polishing stop film) 12 are all removed in the chemical mechanical polishing (CMP) process to isolate the active area from the field area, as Figure 2f shown, the process can be roughly divided into three steps.
[0188] In the first step, bulk CMP is performed on the second insulating film 15 on the platen to achieve local planarization. In the second step, the second insulating film 15 with alleviated steps is cleaned or polished on the platen, and the polishing is stopped when the nitride film (polishing stop film) 12 is exposed. At this time, an end point detection (EPD) can be used to sense the moment when different film materials are exposed. In the third step, the residue of the second insulating film 15 that may remain on the nitride film (polishing stop film) 12 can be removed on the platen, and the nitride film and the oxide film materials are polished for targeting.
[0189] Figure 2g The structure of a chemical mechanical polishing (CMP) device according to an implementation example of the present invention is shown. The device can have three platens. As described above, it can be a structure that sequentially passes through the 1st, 2nd, and 3rd platens for STI CMP polishing of each step. After the polishing is completed, it moves to the cleaning section, and after the cleaning is completed, the process is terminated.
[0190] In addition, in the manufacturing method of a semiconductor device according to an implementation example of the present invention, the method of simultaneously polishing a silicon oxide film, a silicon nitride film, and a polysilicon film using the slurry composition for chemical mechanical polishing can use the polishing methods and conditions commonly used in the prior art, and there are no special limitations in the present invention.
[0191] The dispersion stability of the slurry composition for chemical mechanical polishing according to an implementation example of the present invention is high. The Ce content on the surface of the cerium oxide particles contained in the slurry composition is high, and it can improve the polishing rate for a silicon-containing substrate based on the chemical polishing mechanism of forming Si-O-Ce between silicon dioxide and cerium. Therefore, even under the condition of a low content of cerium oxide contained, it can be particularly effectively used in removing the silicon oxide film from the surface of a semiconductor device in the CMP process. 3+ content is high, and it can improve the polishing rate for a silicon-containing substrate based on the chemical polishing mechanism of forming Si-O-Ce between silicon dioxide and cerium. Therefore, even under the condition of a low content of cerium oxide contained, it can be particularly effectively used in removing the silicon oxide film from the surface of a semiconductor device in the CMP process.
[0192] The third embodiment of the present invention provides a semiconductor device, which includes:
[0193] A substrate; and a trench located on the substrate and filled with an insulating material, wherein the trench is formed by grinding at least one film selected from a silicon oxide film, a silicon nitride film, and a polysilicon film using a slurry composition for chemical mechanical polishing, and wherein the slurry composition for chemical mechanical polishing contains cerium oxide particles, a solvent, and a surface treatment agent.
[0194] Details of parts overlapping with the first and second embodiments of the present invention are omitted, but the descriptions of the first and second embodiments of the present invention are equally applicable to the third embodiment.
[0195] A fourth embodiment of the present invention provides a method for manufacturing cerium oxide particles for chemical mechanical polishing, which includes the following steps: preparing a raw material precursor; and pulverizing or precipitating cerium oxide particles in a solution containing the raw material precursor to obtain a dispersion of cerium oxide particles for chemical mechanical polishing.
[0196] Details of parts overlapping with the first to third embodiments of the present invention are omitted, but the descriptions of the first to third embodiments of the present invention are equally applicable to the fourth embodiment.
[0197] In one implementation example of the present invention, the step of preparing a raw material precursor may be included. The raw material precursor may be any precursor substance capable of manufacturing cerium oxide particles as a product.
[0198] In one implementation example of the present invention, the step of pulverizing or precipitating cerium oxide particles in a solution containing the raw material precursor to obtain a dispersion of cerium oxide particles for chemical mechanical polishing may be included. The step of pulverizing cerium oxide particles in a solution containing the raw material precursor can be pulverized by, for example, a pulverization process, and the pulverization method can be determined within the common technical knowledge of those skilled in the art without limitation. The step of precipitating cerium oxide particles in a solution containing the raw material precursor to obtain a dispersion of cerium oxide particles for chemical mechanical polishing may further include the step of removing the supernatant; or a filtration step.
[0199] In particular, in one implementation example of the present invention, the overall process of particle synthesis can be carried out at room temperature and does not experience an alkaline pH. Therefore, it has the advantage of being able to exhibit the characteristics of the above-mentioned particles while achieving a highly energy-efficient manufacturing process.
[0200] Industrial Applicability
[0201] According to an embodiment of the present invention, the manufactured cerium oxide particles increase Ce on the surface of cerium oxide 3+The proportion, although the particle size is small, when included in the slurry composition for chemical mechanical polishing, even with a low content, can have a high oxide film removal rate. When combined with the surface treatment agent disclosed in the present invention, by converting the surface zeta potential of the cerium oxide particles into a negative value, it is possible to expand applications such as nitride film polishing, and compared with when no additive is added, improved effects can be obtained simultaneously, thus having industrial applicability.
Claims
1. A slurry composition for chemical mechanical polishing, characterized in that, it comprises: cerium oxide particles; a solvent; and a surface treatment agent, wherein the surface treatment agent converts the Zeta potential on the surface of the cerium oxide particles into a negative value (-), and in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt%, the average light transmittance for light with a wavelength of 450 to 800 nm is 50% or more.
2. The slurry composition for chemical mechanical polishing according to claim 1, characterized in that, before adding the surface treatment agent, the Zeta potential of the cerium oxide particles is 1 to 80 mV in the range of pH 2 to 8.
3. The slurry composition for chemical mechanical polishing according to claim 1, characterized in that, after adding the surface treatment agent, the Zeta potential of the cerium oxide particles is -80 to -1 mV in the range of pH 7 to 10.
4. The slurry composition for chemical mechanical polishing according to claim 1, characterized in that, based on the total weight of the slurry composition for chemical mechanical polishing, the content of the surface treatment agent is 0.001 to 1 wt%.
5. The slurry composition for chemical mechanical polishing according to claim 1, characterized in that, the surface treatment agent is at least one selected from hydroxyethylidene diphosphonic acid, aminotrimethylenephosphonic acid, 2-phosphonobutane-1,2,4-tricarboxylic acid, ethylenediaminetetramethylenephosphonic acid, ethylenediaminetetraacetic acid, nitrilotriacetic acid, diethylenetriaminepentaacetic acid, N-hydroxyethylethylenediamine-N,N',N'-triacetic acid, triethylenetetraminehexaacetic acid, 1,2-diaminopropanetetraacetic acid, 1,3-diamino-2-hydroxypropane-N,N,N′,N′-tetraacetic acid, N-hydroxyethyliminodiacetic acid, dihydroxyethylglycine, ethylene glycol ether diamine tetraacetic acid, 1,2-diaminopropane-N,N,N′,N′-tetraacetic acid, ethylenediaminetetraacetic acid, and their salts.
6. The slurry composition for chemical mechanical polishing according to claim 1, characterized in that, the surface treatment agent is hydroxyethylidene diphosphonic acid or ethylenediaminetetraacetic acid.
7. The slurry composition for chemical mechanical polishing according to claim 1, characterized in that, based on the total weight of the slurry composition for chemical mechanical polishing, the content of the cerium oxide particles is 0.001 to 5 wt%.
8. The slurry composition for chemical mechanical polishing according to claim 1, characterized in that, the slurry composition for chemical mechanical polishing further comprises a pH regulator, The pH regulator is an inorganic acid, an organic acid, an amino acid, imidazole, an alkylamine, an alkanolamine, a quaternary ammonium base, ammonia, or a combination thereof, wherein the inorganic acid is one or more selected from sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid, the organic acid is one or more selected from acetic acid, citric acid, gluconic acid, glycolic acid, formic acid, lactic acid, malic acid, carotinic acid, maleic acid, oxalic acid, phthalic acid, succinic acid, and tartaric acid, and the amino acid is one or more selected from lysine, glycine, alanine, arginine, valine, leucine, isoleucine, methionine, cysteine, proline, histidine, phenylalanine, serine, tris(hydroxymethyl)methylglycine, tyrosine, aspartic acid, tryptophan, and aminobutyric acid.
9. The slurry composition for chemical mechanical polishing according to claim 1, wherein, the pH value of the slurry composition for chemical mechanical polishing is 2 to 10.
10. The slurry composition for chemical mechanical polishing according to claim 1, wherein, The slurry composition for chemical mechanical polishing has a silicon oxide film polishing rate.
11. The slurry composition for chemical mechanical polishing according to claim 1, wherein, the secondary particle size of the cerium oxide particles measured by a dynamic light scattering particle size analyzer is 1 to 20 nm.
12. The slurry composition for chemical mechanical polishing according to claim 1, wherein, the primary particle size of the cerium oxide particles measured by a transmission electron microscope is 0.5 to 10 nm.
13. The slurry composition for chemical mechanical polishing according to claim 1, wherein, Based on X-ray photoelectron spectroscopy analysis, taking 100% of the total XPS peak area representing the Ce-O binding energy on the surface of the cerium oxide particles as a reference, the sum of the XPS peak areas of the Ce-O binding energy of Ce 3+ is 30% or more.
14. The slurry composition for chemical mechanical polishing according to claim 1, wherein, the cerium oxide particles are made by a step of obtaining a dispersion of particles by precipitation in a solution containing a raw material precursor and at an acidic pH.
15. A method for manufacturing a semiconductor device, wherein, it includes a step of polishing using the slurry composition for chemical mechanical polishing according to claim 1.